Exploring Fire Incidents/Accidents Onboard Cruise and Passenger Ships - Ventikos, Nikolaos P. (SPOUDAI Journal of Economics and Business, 2013)
The aim of this paper is to present aspects of the implemented statistical analysis and patterns of the recorded maritime fire accidents. In this context, a focused database was created taking into account the specific sources for the data available; hence, the data was collected from selected cruise/passenger operators which provided information regarding the events of ignition, and generally smaller or bigger fires which took place onboard vessels. A key achievement of this effort is the healing of the usual problem of underreporting of fire accidents; in particular, underreporting small fires in relative (commercial) databases is a common problem in drawing reliable and usable risk related conclusions. However, the results presented in this paper are based upon a rather complete set of fire records providing this way for reality reflecting results and error free conclusions. Based on this database, the paper presents the results derived by statistical analysis which are able to provide patterns and trends of fires onboard passenger and cruise vessels. Furthermore, information about actually recorded occurrences/frequencies in relation to fire ignition and fire development is also included. This approach allows exploring, in a quantitative manner, the issue of fires for the examined fleet by giving specific figures regarding the frequency of events per ship-year, and the expected number of events per year. Finally, a series of tests is performed to identify whether the recorded patterns and relationships are statistically significant observations or whether they are solely attributable to chance. The paper concludes with insights drawn from the aforementioned topics. JEL Classifications: R41; L91; Y1.